2019
DOI: 10.3747/co.26.4203
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Combined Androgen Blockade with Antiandrogen for Advanced Prostate Cancer

Abstract: Background Combined androgen blockade (cab) is a promising treatment modality for prostate cancer (pca). In the present meta-analysis, we compared the efficacy and safety of first-line cab using an antiandrogen (aa) with castration monotherapy in patients with advanced pca.Methods PubMed, embase, Cochrane, and Google Scholar were searched for randomized controlled trials (rcts) published through 12 December 2016. Hazard ratios (hrs) with 95% confidence intervals (cis) were determined for primary outcomes: over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Prostate cancer (PCa) has become a leading cause of cancer-related mortality among men worldwide (1)(2)(3). In addition, as the population ages, prostate cancer rates are likely to increase (4).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) has become a leading cause of cancer-related mortality among men worldwide (1)(2)(3). In addition, as the population ages, prostate cancer rates are likely to increase (4).…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy combined with bicalutamide was not routinely recommended for metastatic castration-sensitive PCa in international guidelines. However, this combined treatment was still used in some patients in China, since several retrospective studies and meta-analyses showed that this regimen may bring survival benefits to some patients with advanced PCa [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 For first-generation antiandrogens, the recommendation for M0 disease is based on evidence from meta-analyses. 26 Compared with castration monotherapy, CAB plus an NSAA was associated with significantly improved OS and PFS.…”
Section: Clinical Interpretationmentioning
confidence: 98%
“…Six papers were obtained that reported on combination therapies versus castration 12,[26][27][28][29][30] comprising two metaanalyses, 26,27 two RCTs, 12,30 and two large retrospective studies. 28,29 Two meta-analyses reported on combined androgen blockade versus castration.…”
Section: Literature Review Update and Analysismentioning
confidence: 99%